If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -8 + 3x = 19 Combine like terms: 9 + -8 = 1 1 + 3x = 19 Solving 1 + 3x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3x = 19 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = 19 + -1 3x = 19 + -1 Combine like terms: 19 + -1 = 18 3x = 18 Divide each side by '3'. x = 6 Simplifying x = 6
| 3-4=8x+3 | | 2y-15=7 | | -2(-9+6a)-(3a-2)=8a-3a | | 2x^2+12x-8=0 | | x^2+2x=440 | | x^2-2x=440 | | 4x=21+2.5x | | 4a+3-7=-19 | | -8+y=-24 | | 4x=5x-1 | | 10-(-2)+4(-a-5)=-20 | | 3u^2+12u=0 | | -6(-a+5)=23 | | 4(x-2)+7=1-3(1-3x) | | -7(3a+4)=14 | | 3(7a+2)=48 | | 5(3+2x)=55 | | 4x+11=93-9x | | 7-(15+3x)=11x-(5x-19) | | 2(5y-2)=3(2y+3)+3 | | 4(3+6)= | | 4x^2-17x=18 | | 3(1-2(-1))=x | | -5h+4=3h+20 | | 3x+5=9+5x | | x^4y-2x^2y+y=0 | | t-(-29)=29 | | 15(y-4)-(y-9)+5(y+6)=0 | | -5x+9x=-(x-2)-7(5x+6) | | 13=x-13 | | -9=h+47 | | 3y+3=-6 |